Mediators of Sepsis - Lamy, Maurice; Thijs, Lambert G. (Springer Berlin Heidelberg, 1992)
This volume contains contributions by well-known scientists and clinicians in the fields of microbiology, infectious diseases, physiology, internal medicine, surgery, anaesthesiology, and intensive care medicine. It provides an up-to-date overview of the mediators and pathophysology of sepsis and septic shock as well as the latest therapeutic approaches
Keywords: Intensive / Critical Care Medicine; Emergency Medicine; Internal Medicine; Surgery; Critical care medicine; Emergency medicine; Internal medicine; Mediator; Übertragung; Sepsis; Aufsatzsammlung